Rayy : from its origins to the mongol invasion : an archaeological and historiographical study - Rante, Rocco. (Arts and Archaeology of the Islamic World, 2014)
This book offers a new history of the ancient city of Rayy. Based on the results of the latest excavations on the Citadel and the Shahrestan (the political and administrative nucleus of the city in all periods), the study of historical and geographical texts and on surveys carried out between 2005 and 2007 by the author and the Iranian archaeologist, Ghadir Afround, the complete occupation sequence of the city, from its foundation in the Iron Age and the Parthian reconstructions (2nd to 1st centuries BC), up to the Mongol invasions and rapid depopulation in the 13th century CE, comes to light.